Multi-objective optimization of sandwich composite pressure hull for decreasing weight and drag force and increasing buckling load capacity. Issue 1 (December 2020) - Helal, Mahmoud; Fathallah, Elsayed
Abstract: In underwater applications, space vehicles, and aircrafts, the weight becomes an important factor. Additionally, the design of composites structures greatly depends on the number of layers and the fiber orientation angle. Therefore, this work presents the optimization of sandwich composite pressure hull in order to minimize (weight and drag force) and maximize the buckling load capacity using ANSYS Parametric Design Language (APDL). Tsai-Wu and maximum stress failure criteria were incorporated for predicting the first-ply failure. The major and minor radius of the pressure hull, the ring and long beams dimensions, the fiber orientation angle and layer thickness are taken as design variables. The results illustrated that, core thickness ( Tcore ) has a great effect to resist the shell buckling. While, has a little effect on both Tsai-Wu and maximum stress failure index.